2022
DOI: 10.1093/brain/awac084
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation of striatal dopamine, brain metabolism and cognition in dementia with Lewy bodies

Abstract: Dementia with Lewy bodies, the second most common neurodegenerative dementia, is characterized by cognitive decline, fluctuation of cognition and alertness, visual hallucinations, rapid eye movement sleep behavior disorder, and parkinsonism. Imaging biomarkers are of great importance in diagnosing patients with DLB and associated with characteristic clinical features including cognitive decline. In this study, we investigate interrelation between nigrostriatal dopamine depletion, brain metabolism, and cognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…To the best of our knowledge, our study is the first report demonstrating these associations. A very recent multimodal neuroimaging study (n=55) has pointed to an association between nigrostriatal degeneration (as assessed by dopamine transporter SPECT) and cortical hypometabolism in clinical DLB (44). However, such associations had neither been assessed using neuropathologic evaluations nor in the context of clinical AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, our study is the first report demonstrating these associations. A very recent multimodal neuroimaging study (n=55) has pointed to an association between nigrostriatal degeneration (as assessed by dopamine transporter SPECT) and cortical hypometabolism in clinical DLB (44). However, such associations had neither been assessed using neuropathologic evaluations nor in the context of clinical AD.…”
Section: Discussionmentioning
confidence: 99%
“…However, such associations had neither been assessed using neuropathologic evaluations nor in the context of clinical AD. Additional studies combining FDG-PET with imaging modalities aimed to evaluate SN degeneration in-vivo (44)(45)(46)(47) would be of great interest for replicating and studying these associations in larger observational cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, regional cerebral hypoperfusion or hypometabolism in neurodegenerative disorders reflects the underlying neuronal dysfunction and can potentially be used as diagnostic and predictive biomarkers 23‐26 . Our recent previous study also showed that hypometabolism associated with nigrostriatal degeneration was significantly associated with cognitive dysfunction in patients with dementia with Lewy bodies 27 . Conversely, the role of hyperperfusion or hypermetabolism in neurodegenerative disorders remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…[23][24][25][26] Our recent previous study also showed that hypometabolism associated with nigrostriatal degeneration was significantly associated with cognitive dysfunction in patients with dementia with Lewy bodies. 27 Conversely, the role of hyperperfusion or hypermetabolism in neurodegenerative disorders remains unclear. Moreover, previous studies reported that dopamine deficiency in dopaminergic inhibitory neurocircuits would result in enhanced oscillatory burst activity of the basal ganglia, 28,29 leading to increased brain metabolism in areas exhibiting PDRP activity, which was ameliorated after levodopa infusion.…”
Section: Discussionmentioning
confidence: 99%
“…In specific, decreased brain function mediates the effects of Aβ or tau uptake on cognition 22,23 . Similarly, metabolic or perfusion changes are associated with progression, 24 clinical symptoms, 25 and cognitive dysfunction in DLB 26 . However, increased brain function may be associated with worse cognition in DLB 27,28 .…”
Section: Introductionmentioning
confidence: 99%